The Correlation of the Family Support with An Anxiety Level of Coronary Heart Disease on Patients - Siti Santy Sianipar; Suryagustina Suryagustina; Evie Eko Indriyani (Universitas Sari Mulia, 2021)
Latar Belakang: Penyakit Jantung Koroner merupakan penyakit penyebab kematian tertinggi dan juga merupakan penyakit yang tergolong susah disembuhkan serta sering menimbulkan kematian mendadak. Kurangnya dukungan keluarga dapat meningkatkan kecemasan pada pasiensehingga dapat mempengaruhi proses penyembuhan. Untuk itu dukungan dari keluarga pada pasien PJK merupakan faktor penting dalam mengurangi tingkat kecemasan.Tujuan : Penelitian ini bertujuan mengetahui hubungan dukungan keluarga dengan tingkat kecemasan pada pasien Penyakit Jantung KoronerMetode: adalah korelasional dengan uji statistik Spearman Rank. Pengambilan sampel menggunakan Purposive Sampling sebanyak 30 responden.Hasil:Tingkat kecemasan nilai p value 0,000 â‰¤ nilai ï¡ = 0,05, maka Ha1 diterima dimana ada hubungan antara dukungan keluarga dengan tingkat kecemasan.Simpulan: Ada hubungan antara dukungan keluarga dengan tingkat kecemasan. Saran yang diajukan yaitu memberikan pendidikan kesehatan kepada keluarga pasien PJK tentang pentingnya dukungan keluarga dalam mengurangi tingkat kecemasan dalam proses pengobatan.Kata Kunci: Penyakit Jantung Koroner (PJK), Tingkat Kecemasan, Dukungan KeluargaÂ Background: Coronary Heart Disease was the high cause of death and is also a commonly curable and often sudden death. Lack of family support can increase patient anxiety and thus affect the healing process. For that, support from the family in patients with Coronary Heart Disease is an important factor in reducing anxiety levels.Purpose: This study was meant to know a correlation of the family support with an anxiety level of Coronary Heart Disease on patientsMethods: Of this study was correlational with the statistic test of Spearman Rank. Taking this sample used purposive sampling as much total of 30 respondentsResult: Of this study was an anxiety level, the p-value of 0.000 â‰¤ the value ofÂ ï¡ = 0.05, so that Ha 1 was accepted where there was a correlation of the family support with an anxiety level.Conclusion: There was a correlation between family support and anxiety level. The suggestion raised was to give health education to the patientâ€™s family of Coronary Heart Disease about the importance of family support in reducing an anxiety level in the treatment process.Â Keyword: Coronary Heart Disease, An Anxiety Level, The Family Support